Intellectual Property of the IFPA Campus Altamira: documental analysis, perception of servers and technological prospection - Castro, Laísa Maria de Resende (2024)
The creation of the Federal Institutes boosted innovation and encouraged Brazil's regional potential. Thus, the IFPA Altamira campus was created to generate intellectual property (IP) and promote innovation in the region. In this sense, this research evaluates the stage of institutional updating of the Altamira campus four years after the promulgation of the Innovation Policy. The paper covers documentary analyses and technological prospecting at INPI. Furthermore, a questionnaire was applied to staff, revealing an initial stage of institutional development of IP and innovation. Most staff were not involved in research with innovative potential. The team had little knowledge of IP, reflected in the absence of patents, software, and industrial design registrations at INPI. However, the research observed that the themes of IP and innovation were present in analyzed curricula. Therefore, it is necessary to insert joint and strategic actions to contribute to the culture of innovation on the campus.